AGING AND PUBLIC EDUCATIONAL POLICIES: PROMOTING LEARNING FOR THE INCLUSION OF THE ELDERLY - da Costa, Josiette de Nazaré Silva (Seven Editora, 2026)
This article discusses the process of population aging in Brazil and educational policies aimed at promoting learning and social inclusion for older adults. Aging is a global phenomenon and is occurring at an accelerated pace. Legal frameworks such as the 1988 Federal Constitution, the National Policy for the Elderly (Law No. 8,842/1994), and the Statute of the Elderly Person (Law No. 10,741/2003, updated by Law No. 14,423/2022) highlight some advances in guaranteeing the right to education for older adults, emphasizing programs such as Youth and Adult Education (EJA) and Open Universities for the Third Age (UnATI), which contribute to active and participatory aging. Lifelong learning is an inclusion strategy, and access to formal and informal education strengthens the self-esteem, autonomy, and socialization of older adults. However, structural barriers persist, such as the absence of specific educational policies, low funding, a shortage of qualified professionals, and ageism in educational institutions. In conclusion, this article argues that public educational policies aimed at aging should be integrated into human rights and citizenship agendas. Investing in the education of older adults is essential to promote active aging, combat ageism, and value age diversity, consolidating a more just and inclusive society.